Cognitive, emotional, and behavioral profile in children and adolescents with chronic pain associated with rheumatic diseases: A case-control study. (July 2019) - Pascali, Maria; Matera, Emilia; Craig, Francesco; Torre, Francesco La; Giordano, Paola; Margari, Francesco; Zagaria, Giuseppina; Margari, Mariella; Margari, Lucia
Background: The prevalence of chronic pain is about 30% in children and adolescents which suffer from severe emotional distress. The aim of this observational study is to investigate cognitive, emotional and behavioral consequences of benign chronic pain in children and adolescents suffering of reumathologic diseases. Materials and Methods: A total of 49 participants, chronic pain participants (CPPs) and controls (CGPs), affected by rheumatic diseases, were enrolled. Assessment included collection of sociodemographic data, pain characteristics, and administration of Visual Analog Scale (VAS), Depression Inventory for Children and Adolescents (CDI), Conners' Parent Rating Scales–Revised (CPRS-R), Child Behavior Checklist (CBCL), and Screen for Child Anxiety–Related Disorders (SCARED). For the statistical analysis, Student's t -test for independent samples and Pearson's correlation were used. The significance value was set at p less than .05. Results: A significant difference of mean scores of CBCL items and of CPRS items between the two groups was found. In CPPs, a significant correlation between VAS and mean scores of several CBCL items and between VAS and mean scores of several CPRS items was found. Conclusion: Chronic pain is a real syndrome in which an interdisciplinary treatment should be applied, considering the psychopathological risk, especially in developmental age.